PENEGAKAN HUKUM OLEH KOMISI PERLINDUNGAN PERSAINGAN USAHA DALAM PENANGANAN PERSAINGAN USAHA TIDAK SEHAT DITENGAH WABAH COVID-19 - Gebrina Ayu Nastiti (Res Judicata, 2020)
The objective of the research is to explore the functions and roles of KPPU (Business Competition Supervisory Commission) in eradicating various monopolistic practices and unfair business competition which occurred in covid-19 case. Since this case has become a global pandemic, some people or business people whom aware about this pandemic deliberately hoard masks, hand sanitizers and resell them in unimaginable high prices, whereas, these two items are urgently needed only for those whose infected Covid-19. There is also information that some hospitals offer a package of rapid test for the public in expensive prices, which limits the ability of the community to testify themselves whether to isolate  independently at home or do the hospital treatment. Law Number 5 Year 1999 concerning monopolistic practices and unfair business competition is used in discussing this research. In this research, it is known that KPPU has not been able to carry out an investigation unless, information and evidence from the parties who feel disadvantaged by the existence of monopoly and unfair business competition were provided. In addition, if however fraud has been detected, the sentence which will be faced by monopolists or unfair business actors is mere an administrative sentence